2018
DOI: 10.1002/14651858.cd005943.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen for treating threatened miscarriage

Abstract: of findings for the main comparison. Progesterone compared to placebo or no treatment for treating threatened miscarriage Progesterone compared to placebo or no treatment for treating threatened miscarriage Patient or population: women with threatened miscarriage Setting: two in high-income countries (Germany and Italy), four in upper-middle income countries (two in Iran, one in Malaysia and one in Turkey) and one in lower-income country (Jordan). All in hospitals (university or women's) or medical centres Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 72 publications
1
58
0
Order By: Relevance
“…Cochrane systematic review (2011) stated that treatment of threatened abortion with progestogens compared to placebo reduced the risk of abortion to 0.47% while no difference regarding preterm labour [6]. Similarly, Lee et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochrane systematic review (2011) stated that treatment of threatened abortion with progestogens compared to placebo reduced the risk of abortion to 0.47% while no difference regarding preterm labour [6]. Similarly, Lee et al…”
Section: Discussionmentioning
confidence: 99%
“…They found that treatment of abortion with progestogens compared to placebo reduced the risk of abortion to 0.47% while no difference regarding preterm labour. They were uncertain about the relation of progestogen to congenital anomalies as the quality of evidence was low [6].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this updated review is to study all available data to determine the efficacy and safety of administering prophylactic progesterone in an attempt to prevent pregnancy loss in the population of women with recurrent miscarriages. There is a separate Cochrane Review on the use of progestogens for treating women with threatened miscarriage (Wahabi 2018). This is an update of a review last published in 2013 (Haas 2013).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Thus, this updated Cochrane Review is in agreement with and includes more trials than prior published systematic reviews. A separate Cochrane Review has also been conducted on the use of progestogens for treating women with threatened miscarriage (Wahabi 2018), and this also suggests a benefit in terms of a reduction in miscarriage in those women treated with progestogens.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
See 1 more Smart Citation